Extra-Abdominal Desmoid Tumours: A Review of the Literature. (15th August 2012) - Molloy, A. P.; Hutchinson, B.; O'Toole, G. C.
Abstract : Extra-abdominal desmoid lesions, otherwise known as aggressive fibromatosis, are slow-growing benign lesions which may be encountered in clinical practice. Recent controversies exist regarding their optimal treatment. Given their benign nature, is major debulking surgery justified, or is it worth administering chemotherapy for a disease process which unusually defies common teaching and responds to such medications? We present a literature review of this particular pathology discussing the aetiology, clinical presentation, and various current controversies in the treatment options.